(3GdKeQ GdjGfY Gddjf aj CMcGe hdZGJ cCjfs - (3YHO GdZfj Hf TGcQ Hf eMeO GdSGOGJ GdOeTbj GdMfaj,J (B1265 (3g` s
(3ChdgG (B:s
(3hHYO, ajbhd gPg CdhcI bdjdI hEf cGfJ Hjf CJQGHgG ebfYI HbfGY GdMSf LdjdI eJVefI s
(3BNQgG (B:s
(3dcGf cdGeg eYJQVkG, aGage hgG gfG hba HfG LhGO GdebGd Yf WQGR gPg GdHQhO GdHjGfjI hCf jYWj GdfXQ eLGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B162 - (3U(B165s
(3HgG fXGe GdJYbjHIs
(3GSe GdeNWhWI ceG hQO PcQg hGVMkG haj OGNd GdeNWhWIs
(3hSejJgG GdRgQ GdjGfYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B274s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B87 s
Keywords: (3GdfMhs